Submental intubation: our experience - Navaneetham, Anuradha (Springer-Verlag, 2010)
INTRODUCTION: Airway management for patients who suffered midfacial fractures is complicated. In maxillofacial injuries, a choice has often to be made between different ways of intubation when surgical access to both the nasal and oral cavities is necessary. Submental intubation technique is an alternative to nasoendotracheal intubation and tracheostomy in the management of patients with severe midfacial fractures. This procedure is simple to do and has a low morbidity. MATERIAL: Submental intubation-paramedian technique has been used in 15 cases from May 2005–April 2007 in Hosmat Hospital, Bangalore. All patients had fractures disturbing the dental occlusion plus either an associated fracture of the skull base or a displaced nasal fracture. RESULTS: Average duration of procedure was 7 minutes. Average duration of tube in vitro after surgery was 20 hours. There were 2 postoperative complications of tube obstruction which were successfully managed. CONCLUSION: Submental intubation demands certain technical skills but it is simple, rapid and may avoid tracheostomy in selected patients.